Establishing an Office-Based Framework for Resuming Otolaryngology Care in Academic Practice During the COVID-19 Pandemic. (March 2021) - Pearlman, Aaron N.; Tabaee, Abtin; Sclafani, Anthony P.; Sulica, Lucian; Selesnick, Samuel H.; Kutler, David I.; Montano, Joseph J.; Levinger, Joshua I.; Suurna, Maria V.; Modi, Vikash K.; Stewart, Michael G.
Objective: The COVID-19 health crisis abruptly disrupted the practice of otolaryngology. This article aims to define the changes needed to operate an academic otolaryngology practice safely and efficiently from within the epicenter of the pandemic. We define the areas of normal patient workflow that have been affected by COVID-19, and we offer mitigation strategies with attention paid to the specific needs of subspecialties. Data Sources: The article includes data specific to the office practice metrics of the Weill Cornell Medicine Department of Otolaryngology–Head and Neck Surgery, as well as publically available data from New York Presbyterian Hospital system and the New York Times . Review Methods: Expert opinion. Conclusions: Through careful planning and execution, it is possible to reestablish safe otolaryngologic patient care during the COVID-19 pandemic. It will require a significant change from prior practice models for successful implementation. Additionally, telemedicine can be positively integrated into the treatment of otolaryngology diseases for new and established patients. Implications for Practice: The information conveyed in this review can be used as a guide by large and small otolaryngology groups to identify aspects of the patient visit that are "at risk" due to COVID-19, and it suggests sensible responses that can be made without a significant disruption to normal practice. The methods used to identify vulnerabilities with the patient visit process can be applied to future unforeseen crises, such as a resurgence of COVID-19 or a novel pandemic.